The Role and Characteristics of National Accounting Standard Setters in the European Union: A Comparative Analysis - José Luis Ucieda Blanco; Beatriz Santos Cabalgante; Domi Romero Fúnez (Revista de Contabilidad: Spanish Accounting Review)
). This poses the question of how these institutions adapt to a changing environment and what factors shape their structure. We provide updated information on 17 National Accounting Standard Setters (NASS) from 15 EU countries plus Australia and USA. The results reveal the four most relevant dimensions of each NASS (nature, organization, financing, and transparency) and identify two main models of NASS (public and private). The paper also discusses potential applications of this data, mainly to examine whether (and how) certain institutional factors could enhance the quality of financial reporting.